2020
DOI: 10.1088/1742-6596/1510/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental analysis of the 3D printed multi-material ankle-foot orthosis

Abstract: The application of 3D printing in medicine is the major area to concern in the nearest future. Namely, it is convenient to additively manufacture the Ankle-Foot Orthosis (AFO) by fused-deposition modeling 3D printer. AFO is the device, used in medicine, to help the patients rehabilitate from the foot drop disease. The shape of the AFO may vary depending on the leg and foot specifications of the patient. In this paper, three models of the AFO were designed to analyze both numerically and experimentally, those a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…However, the fatigue resistance was very low due to the deformation mode of the composite. Otepbergenov et al performed a numerical simulation to determine the high stress concentrations of the ankle-foot orthosis model made by PLA [117]. Nylon was incorporated into the 3D-printed model to reduce high stress concentrations.…”
Section: Thermoplastic Polymers and Compositesmentioning
confidence: 99%
“…However, the fatigue resistance was very low due to the deformation mode of the composite. Otepbergenov et al performed a numerical simulation to determine the high stress concentrations of the ankle-foot orthosis model made by PLA [117]. Nylon was incorporated into the 3D-printed model to reduce high stress concentrations.…”
Section: Thermoplastic Polymers and Compositesmentioning
confidence: 99%
“…A similar use of a dualhead 3D printer is found in medicine by Liimatainen et al [14] when printing models of a tumor-infected organ, where healthy and infected tissues are printed from different material. Another example is in the work of Otepbergen et al [16] the use of multimaterial 3D printing in the preparation of an ankle orthosis made of PLA material which is locally reinforced with Nylon.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that polylactic acid (PLA) is not solely able to meet the required strength for AFOs. Researchers then used PLA with nylon-12 as the printing material to meet the required strength [ 23 ]. Producing AFOs with two materials in different layers has also been investigated to achieve a high strength.…”
Section: Introductionmentioning
confidence: 99%
“…To predict the actual mechanical behavior of the AFOs, researchers have considered the von Mises stress distribution and deformation data. AFOs based on PLA have been evaluated using ANSYS simulation and are being replaced with nylon-12 during production in high-stress-concentration areas to attain a higher strength [ 23 ]. In order to predict the optimal neck size of the lower section of AFOs, different neck sizes of the lower section were considered in the simulation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%